Groups Are More Libertarian than Individuals - Philipp Doerrenberg; Christoph Feldhaus; Felix Kölle; Axel Ockenfels (CESifo GmbH, 2024)
Using a series of controlled laboratory experiments involving decisions to intervene in others' choice opportunities; we find that groups grant more autonomy to others than individuals. This finding is robust across two decision contexts, one involving individual decision-making (Internality) and one involving social decision-making (Externality). Analyses of the group chat logs and two additional experiments show that participants tend to shy away from proposing interventions in social contexts, even when they intervene individually. We conclude that interventions differ systematically between individual and social contexts, and that transferring decision-making power to groups can lead to a "liberal shift".
Keywords: C92; D70; D91; M21; 330; teams; decision making; autonomy; interventions; experiment